The nature and causes of the farm income problem - Attwood, E. A. (Statistical and Social Inquiry Society of Ireland, 1982)
In the current debate on national economic issues, the very grave situation that exists in the agricultural sector has tended to be regarded as of concern only to the farming community. While the impact of the current agricultural difficulties obviously impinges most directly on farmers, it, nevertheless, has most serious consequences for the growth of the economy as a whole, for the level of our balance of payments deficit and for the exchequer position.
Read before the Society, 20 May 1982
Keywords: Farm incomes problem; Irish agriculture; Agricultural incomes; Agricultural inputs and outputs; 314.15